2011
DOI: 10.1007/s00228-011-1073-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pharmacodynamic trajectory of the therapeutic response to paroxetine in Japanese patients with panic disorder

Abstract: The present study revealed that plasma concentration of PAX, 5-HTTLPR genotype, -1019C/G 5-HT(1A) genotype, PAS score at baseline, and adverse effects may influence the therapeutic response to PAX in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
1
16
5
Order By: Relevance
“…Last but not the least, we did not nd the relationship between other gene polymorphisms and treatment response to sertraline. This is inconsistent with previous studies that found the 5-HT1A receptor -1019C/G polymorphism was strongly associated with response to treatment in PD receiving sertraline or paroxetinethe [54,59]. Another study suggested that the genetic variant of the COMT enzyme may be related to treatment response to paroxetine in PD [60].…”
Section: Discussioncontrasting
confidence: 81%
“…Last but not the least, we did not nd the relationship between other gene polymorphisms and treatment response to sertraline. This is inconsistent with previous studies that found the 5-HT1A receptor -1019C/G polymorphism was strongly associated with response to treatment in PD receiving sertraline or paroxetinethe [54,59]. Another study suggested that the genetic variant of the COMT enzyme may be related to treatment response to paroxetine in PD [60].…”
Section: Discussioncontrasting
confidence: 81%
“…However, we failed to find the relationship between others gene polymorphisms and treatment response to sertraline. which is inconsistent with previous studies that found the 5-HT1A receptor − 1019C/G polymorphism was strongly associated with response to treatment in PD receiving sertraline or paroxetinethe [49,53]. In another study suggest that the genetic variant of the COMT enzyme may be related to treatment response to paroxetine in PD [54].…”
Section: Discussioncontrasting
confidence: 81%
“…Body weight ranged from 40–95 kg (57.9±11.4 kg). The PD patients in this study were part of the subject group (n=65) in our previous study 9. Out of 65 patients, 52 subjects with PD without MDD were selected, and their raw data from the clinical evaluations and the genotyping of 5-HTTLPR were used and reanalyzed in the present study.…”
Section: Methodsmentioning
confidence: 99%